Calvinist rhetoric in nineteenth-century America: the Bartlet Professors of Sacred Rhetoric of Andover Seminary - Fehler, Brian (Edwin Mellen Press, 2007)
"God is a god of order" : Federalist era revival culture -- Calvinist rhetoric at Andover -- Classicism and the church : Calvinist recovery of ancient rhetoric -- Calvinist elocution in an age of popular oratory -- Revival history as rhetorical history -- "Eloquence is always a means and not an end" : the Calvinists and rhetoric in nineteenth-century America